SISTEM INFORMASI LAYANAN DIGITAL PUSKESMAS BERBASIS ANDROID - Hasan Basri; Dedin Toyibah; Muhamad Fakhri; Hanafi Dirgantara Musahar; Wina Wati; Riski Nur Idad; Widya Apriliah (Universitas Islam Kuantan Singingi, 2020)
The very rapid development of information technology has proven to play an important role in the accelerated development of information both in the world of industry, government and the world of health, so that it can support the performance of increasing the efficiency, effectiveness and productivity of all elements of society, especially in the world of health, both public and private institutions. or individually or individually, which can encourage the realization of a developed and prosperous society. The health sector is one of the important sectors of development that has the potential to be integrated with the presence of technology. Public health center Bayur Lor. Cilamaya Kulon, Karawang Regency is one of the developing health service centers. The number of patients that continues to increase every day causes new problems in the process of seeking information about patients, the number of patients, the number of visits, total income, and data on existing drug supplies. Because based on the existing problems, the Public health center Bayur Lor. Cilamaya Kulon, Karawang Regency, needs to take advantage of information technology, which can overcome the problems faced, so that public health services can be improved for the realization of the vision and mission of the Public health center Bayur Lor. Cilamaya Kulon. Looking at some of the existing problems, researchers use the waterfall method in making an information system. Applications made in this study are based on android. To facilitate the mention of this application, namely Android-based LAGILEMAS (Public health center Digital Service).